The Phonics Approach Improves Early Reading Skills in Preschoolers Aged 4-5 Years - Husnul Khotimah; Ratno Abidin; Wahono; Wardah Suweleh (Universitas Pendidikan Ganesha, 2023)
The low ability to read in the early stages of children aged 4-5 is due to the absence of teaching reading methods in schools. The purpose of this study is to explore and identify the early reading abilities of children aged 4-5 years through the implementation of the phonics approach. This type of research uses qualitative research with a descriptive approach. The subjects in this study were group A, aged 4-5 years, with as many as 18 children, ten boys, and eight girls. Methods of data collection through observation, interviews, and documentation. The research instrument used interview guidelines and research observation sheets. The data analysis technique uses the following steps: data collection, data reduction, data presentation, and conclusion or verification. Based on the findings and discussion, the application of the phonics approach as an alternative method that is very effective and efficient is considered capable of dealing with lazy reading in early childhood. The implication of implementing a phonics approach using various media is very young for children in exploring early reading skills. Thus this phonics approach method is very feasible to be applied to early childhood in improving early reading learning at school.